2016
DOI: 10.1038/sc.2016.110
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular response during urodynamics in individuals with spinal cord injury

Abstract: Individuals with cervical SCI, DSD, poor bladder compliance or >2 years after SCI were associated with a higher possibility of developing AD during urodynamics. Furthermore, AD was more severe in complete (AIS A) individuals and was exacerbated with time after injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…In line with the literature [ 37 ], our AD patients with an AIS A lesion demonstrated a significantly greater decrease in HR than those with an AIS B–D lesion, indicating that the greater the extent of the injury, i.e., the fewer efferent fibers are spared to uphold central sympathetic control of the heart, the greater the influence on HR by the parasympathetic nervous system. In contrast to our observation, Giannantoni et al [ 27 ] reported that AD did not correlate with the completeness of a lesion.…”
Section: Discussionsupporting
confidence: 89%
“…In line with the literature [ 37 ], our AD patients with an AIS A lesion demonstrated a significantly greater decrease in HR than those with an AIS B–D lesion, indicating that the greater the extent of the injury, i.e., the fewer efferent fibers are spared to uphold central sympathetic control of the heart, the greater the influence on HR by the parasympathetic nervous system. In contrast to our observation, Giannantoni et al [ 27 ] reported that AD did not correlate with the completeness of a lesion.…”
Section: Discussionsupporting
confidence: 89%
“…Table 6 displayed the incidence of autonomic dysfunction of the patients with dysuria after high level SCI was very high (about 79.17%, adding B and C), most of them were hyperactivity (62.50%), and a few were hypoactivity (16.67%). NDSD [8] of group B and C was very high, that of high abdominal pressure of group B, C (53.33%, 87.50%) was evidently more quantity than that of group A (25.00%), the ratio of bladder disappearance of group B, C (30.00%, 25.00%) was fewer than that of group A (50.00%). From Table 8, compared with the baseline, it can be demonstrated that the values of SBP and DBP of a typical case at he time of stopping filling increased more than 20 mmHg.…”
Section: Resultsmentioning
confidence: 84%
“…AD is an abnormal autonomic reflex responding to nociceptive stimuli below the level of injury, which develops in patients with high-level SCI (usually above T6). 77,78 A remarkable rise in blood pressure during AD sometimes leads to serious complications, such as intracranial hemorrhage and lethal arrhythmias. 77 Physicians should remove the causes of stimuli as soon as possible and deal with the hypertensive crisis (LoE 5, GoR B).…”
Section: Admentioning
confidence: 99%